Population pharmacokinetic modelling for dose optimization of esomeprazole to treat early-onset preeclampsia - Semere, Gebreyesus Manna (Division of Clinical Pharmacology, 2021)
Rationale Esomeprazole is a proton pump inhibitor with preclinical efficacy data showing it lowers concentrations of soluble fms like tyrosine kinase 1 (sFlt-1) and soluble endoglin (sEng), pathognomonic biomarkers identified in preeclampsia. A randomized controlled trial, Preeclampsia Intervention with Esomeprazole (PIE) trial, was conducted in South African women diagnosed with early-onset preeclampsia to investigate efficacy, but it found no change in clinical outcome or biomarker concentrations. It was hypothesized that the 40 mg daily oral dose was not enough to achieve therapeutic exposure. This study investigated the pharmacokinetics of esomeprazole in patients with early- onset preeclampsia with the aim to optimize the dose for future clinical trials. Methods Pharmacokinetic data from ten pregnant patients with early-onset preeclampsia from the PIE trial, median (range) age 30 (21-43) years, weight 98.8 (56-126) kg, and gestational age 29 (26- 31) weeks, were included for model development. In addition, pharmacokinetic data from non- pregnant healthy volunteers consisted of a pooled dataset of 26 male and female subjects, median (range) age of 21 (18-27) years and weight 69 (54-89) kg, who received 40 mg esomeprazole daily. Analysis of the pharmacokinetic data in pregnant patients was performed using nonlinear mixed-effects modelling with allometric scaling on clearance (CL) and volume of distribution (Vd). Metabolite to parent area under the time-concentration curve (AUCsulf/AUCeso and AUChyd/AUCeso) ratios were compared between pregnant and non-pregnant to assess metabolic changes in pregnancy. Simulations were performed with the model to determine the nonlinear increase in AUC with higher doses and with repeated dosing in the pregnant patients. Simulation results were compared with the preclinical target unbound concentration (0.917 mg/L) and preclinical target unbound AUC0-24 (9.29 mg·h/L). Results A one compartment pharmacokinetic model with first-order elimination and transit compartment absorption best described the data. Model estimated apparent CL and apparent Vd (95% CI) were 19.2 (14.2-26) L/h and 44.2 (29.9-56.6) L, respectively. Median AUCsulf/AUCeso (IQR) for pregnant patients, 2.00 (1.35-2.61) , was significantly higher than that for non-pregnant subjects on day1, 0.700 (0.636-1.00) , and day5, 1.18 (0.981- 1.58) . Median AUChyd/AUCeso (IQR) for pregnant patients, 0.0543 (0.0500-0.0914) , was not significantly different from that of non-pregnant subjects on day5, 0.0777 (0.0569-0.108) but lower than that of non-pregnant subjects on day1, 0.188 (0.156- 0.227). Simulation results showed that predicted steady state unbound Cmax is between 0.0949 and 0.398 mg/L while the predicted unbound AUC0-24 in pregnant patients with the highest dose of esomeprazole used clinically, i.e.120 mg BID, is between 0.696 and 2.92 mg·h/L. Discussion/Conclusion Model estimated CL/F and Vd/F are higher than values previously reported by other population pharmacokinetic models. AUCm/AUCp comparisons showed that esomeprazole metabolism in pregnancy appears to have shifted to the CYP3A4 pathway. This means that the nonlinear AUC increase expected with dose escalation and with repeated dosing are not as significant as in nonpregnant. Simulations indicate that pregnant patients are unlikely to achieve the target concentration and exposure with the highest dose of esomeprazole registered. Further research is necessary to determine the target site of action of esomeprazole in preeclampsia, and the pharmacokinetic metric that correlates with efficacy.